2018
DOI: 10.4103/abr.abr_54_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparison the Effects of Oral Tizanidine and Tramadol on Intra- and Post-operative Shivering in Patients Underwent Spinal Anesthesia

Abstract: Background:Heat loss and core-to-peripheral redistribution of body heat occur in patients undergoing neuraxial anesthesia resulted to decrease of core temperature and early reach of shivering threshold. Because shivering has deleterious metabolic and cardiovascular effects, it should ideally be prevented by pharmacologic or other means. Tizanidine is an alpha-2 agonist. We evaluated the usefulness of oral tizanidine (TI) and tramadol in preventing of shivering in patients undergoing spinal anesthesia for trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
0
0
Order By: Relevance
“…Our trial showed that oral tramadol was effective in reducing the incidence, frequency, duration and severity of post-spinal shivering and meperidine consumption. In agreement with our results, tramadol was reported to be effective in decreasing the incidence and severity of shivering after spinal or general anaesthesia [ 5 , 25 27 ]. Our study results showed that the efficacy of anti-shivering medications greatly varies between its prophylactic and therapeutic uses.…”
Section: Discussionsupporting
confidence: 93%
“…Our trial showed that oral tramadol was effective in reducing the incidence, frequency, duration and severity of post-spinal shivering and meperidine consumption. In agreement with our results, tramadol was reported to be effective in decreasing the incidence and severity of shivering after spinal or general anaesthesia [ 5 , 25 27 ]. Our study results showed that the efficacy of anti-shivering medications greatly varies between its prophylactic and therapeutic uses.…”
Section: Discussionsupporting
confidence: 93%
“…In a study conducted by Adinehmehr et al 20 oral tizandine and tramadol were comparable in respect to their effect in decreasing the incidence and intensity of shivering when used prophylactically in patients under spinal anaesthesia which was similar to our study. Mittal et al 21 in 2014 evaluated the effects of dexmedetomidine and tramadol on haemodynamics and shivering after spinal anaesthesia and concluded that tramadol is as effective as dexmedetomidine in reducing shivering rate, nausea and vomiting.…”
Section: Discussionsupporting
confidence: 89%
“…Both drugs were found to be equally effective. 23 In a research conducted by Bozgeyik et al, dexmedetomidine was administered in conjunction with tramadol. Both medications demonstrated equivalent efficacy in the prevention of shivering.…”
Section: Discussionmentioning
confidence: 99%